Village Midline Study – Site Analysis Report for Doggoh, Lawra-Jirapa, Ghana (GH-0108) - Jasaw, Godfred Seidu; Adams, Mujeeb; Asani, Abass; Kpeno, Emma; Terkpen, Josephine Yuora; Ouédraogo, Mathieu; Cramer, Laura K. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2018)
The village midline survey (VMS) was carried out from the 2nd -12th July, 2018 in Doggoh village. The aim of the VMS was to assess the performance of the indicators around natural resource, organizational landscape and information networks and the changes that have occurred since the baseline (VBS) in 2011. A participatory approach was adopted. Whole community for a were conducted and later, focus group discussions (FGD) were held separately for men and women. The men and women were purposively sampled during the whole community meeting, after which 15 members were randomly selected for each category. The protocols that were used during the VBS were the same ones used for this VMS.